Pengembangan Video Interaktif Berbasis Etnosains Papua untuk Pengajaran IPA Terpadu - Kumalasari, Lina; Irianti, Mustika; Rumagesan, Tamsi Nurfadia (UNIB Press, 2025)
This study discussed the development of Integrated Science teaching materials in the form of an Interactive Video Based on Papua's Local Ethnoscience. The local wisdom of Papua explained in the video includes sago trees, red fruit, matoa trees, and areca nut trees. This research used research and development (R&D) methods with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study include one subject matter expert teacher, one media expert lecturer, and seventh-grade students from SMP Negeri 26 in Sorong Regency. The instruments used to assess the feasibility of the interactive video based on Papua's local ethnoscience include a feasibility sheet by subject matter and media experts, a questionnaire to gauge students' responses to the use of the interactive video, and pretest and posttest trials to evaluate the effectiveness of the interactive video based on Papua's local ethnoscience. The data analysis results showed a score of 97.92% from the subject matter expert and 86.98% from the media expert, both of which fall into the very feasible category. The effectiveness of the Interactive Video Based on Papua's Local Ethnoscience was measured by student learning outcomes, which were categorized as high, with an n-gain score of ≥ 0.7. The students' responses indicated that 15 students 87% gave positive feedback on the use of the Interactive Video Based on Papua's Local Ethnoscience.